THE EFFECT OF WORDWALL PLATFORM ON STUDENTS’ READING COMPREHENSION AT MTS LABORATORIUM JAMBI - Agustin, Dhilla; Monalisa; Fitria, Wahyuni (JR-ELT (Journal of Research in English Language Teaching), 2025)
This research aims to determine the effect of using Wordwall Platform on students’ reading comprehension at MTs Laboratorium UIN Sultan Thaha Saifuddin Jambi. It was quantitative research with a quasi experimental design. The sample of this study was 29 students of experimental class and 29 students of control group using custler random sampling techniques. The data collection instrument in this research was a short essay test consisting of pre-test and post-test. Based on data analysis from research and hypothesis testing carried out, the effect in learning outcomes shows that the average in the experimental class is in the medium category, while the average in the control class is in the low category. It  could be seen  from the pre-test result before  treatment and post-test result after treatment in both of group. It mean score of pre-test of experimental class was 55,86 and the mean score of post-test was 76,03. Meanwhile, the mean score of pre-test in control class was 57,59, and the mean score of post-test was 69,14. This is also shown in the results of the post-test t test. Both of class from pre-test and post-test score got a normality and homogeneity data with significant (0,05). The results of the t test analysis show that the t-count is 3.699 with a significance of 0.01, the significance value shows 0.01<0.05 so that ( is accepted. It can be concluded that Wordwall Platform Effective  for teaching and assessment in Reading Comprehension of Recount Text to class VIII MTs Laboratorium UIN Sultan Thaha Saifuddin Jambi.